IMPLEMENTATION OF CERTAINTY FACTOR IN AN EXPERT SYSTEM FOR DIAGNOSING ORAL CANCER - Nurhasan Nugroho; Nurdiana Handayani; Rachmat Destriana; Tia Ernawati (Jurnal Riset Informatika, 2021)
Oral cancer or oral cavity cancer is cancer that attacks the epithelial tissue of the oral mucosa. Cancer is a disease with a high mortality rate. Therefore, it is very important to be able to provide knowledge assistance to people who are still quite low in knowledge about cancer, especially oral cancer. One way to help diagnose disease is to use an expert system. In this study, an expert system application was developed to diagnose oral cancer based on symptoms and produce a diagnosis and treatment solution. The expert system developed using the certainty factor algorithm (CF). Where is able to overcome uncertainty by providing a value level of trust from experts and users. From the results of the accuracy test, it shows a value of 87%, so the system can function properly.